2021
DOI: 10.52547/rbmb.10.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting Levels of Indoxyl Sulphate among Critically Ill Patients with Acute Nephrotoxicity; Correlations Between Indoxyl Sulphate Levels and Patients’ Characteristics

Abstract: Background: Many animal studies suggested that the uremic toxin indoxyl sulphate can add to renal damage following induced nephrotoxicity and this effect has not been proved in patients with such complication. Methods: This is a prospective, case-control, and an observational study conducted on 74 critically ill patients with acute nephrotoxicity. It was designed to measure serum levels of indoxyl sulphate on the day of enrollment and over the course of their illness using high performance liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The relative heterogeneity concerning sample size, population background, clinical setting, the timing of measurements, and severity of AKI may limit the interpretation of the data. The kinetics of IS accumulation appear to follow those of serum creatinine [ 103 ], and two studies showed that IS levels increase with the severity of AKI [ 104 , 105 ], the highest observed among patients presenting with severe AKI and those who needed renal replacement therapy support. Except for one study reporting a particularly high level [ 71 ], the observed level of total IS remained relatively low compared to that in CKD [ 106 ], ranging from 0.64 to 3.33 µg/mL.…”
Section: Gut-derived Protein-bound Uremic Toxins and Cardiovascular D...mentioning
confidence: 99%
See 2 more Smart Citations
“…The relative heterogeneity concerning sample size, population background, clinical setting, the timing of measurements, and severity of AKI may limit the interpretation of the data. The kinetics of IS accumulation appear to follow those of serum creatinine [ 103 ], and two studies showed that IS levels increase with the severity of AKI [ 104 , 105 ], the highest observed among patients presenting with severe AKI and those who needed renal replacement therapy support. Except for one study reporting a particularly high level [ 71 ], the observed level of total IS remained relatively low compared to that in CKD [ 106 ], ranging from 0.64 to 3.33 µg/mL.…”
Section: Gut-derived Protein-bound Uremic Toxins and Cardiovascular D...mentioning
confidence: 99%
“…On the other hand, systemic inflammation and fluid accumulation, resulting in a decrease in serum albumin levels, may also reduce the measured total serum level of IS, particularly in septic AKI. Two studies analysed the correlation between IS levels and recovery from AKI [ 104 , 105 ], and one study reported an independent association between total IS levels at AKI diagnosis and 90-day mortality [ 107 ]. In addition, the complications of AKI patients may depend on the elimination time course of PBUTs, reflecting the AKI recovery rate independently from renal replacement therapy.…”
Section: Gut-derived Protein-bound Uremic Toxins and Cardiovascular D...mentioning
confidence: 99%
See 1 more Smart Citation